DETERMINAN PRODUKSI PADI DI INDONESIA: KONTRIBUSI LUAS AREAL PANEN DAN KREDIT USAHA PERTANIAN: Determinants Of Rice Production In Indonesia: Contribution Of Harvest Area and Agricultural Business Kredit - Masani, Sab’ul; Asasandi, I Gusti Ngurah Aryawan (Ganec Swara, 2026)
Rice production plays a vital role in national food security due to the high per‑capita consumption of rice in Indonesia. This study examines the effects of harvest area and agricultural business credit on rice production in Indonesia using a quantitative time‑series approach with data from the Central Statistics Agency, the Financial Services Authority, and other relevant institutions. Data were analyzed via multiple linear regression accompanied by classical assumption tests. The results indicate that harvest area exerts a positive and significant effect on rice production (t = 25.37098, p = 0.0000), and agricultural business credit also has a significant positive effect (t = 10.69196, p = 0.0000). Jointly, these variables significantly influence rice production (F = 331.9887, p = 0.0000). Moreover, the model’s R² = 96.09% suggests that variations in rice production are largely explained by harvest area and agricultural credit. These findings underscore the importance of protecting agricultural land and strengthening access to productive financing to sustain national rice production